Liquidity constraints, real estate regulation, and local government debt risks - Xiao-Li Gong; Jin-Yan Lu; Xiong Xiong; Wei Zhang (Financial Innovation)
Abstract Given the existence of real estate market bubbles and risks arising from high government debt, countries are faced with the challenge of preventing systemic risks. This study investigates the macroeconomic dynamics of the real estate market and local government debt risk from the perspective of liquidity constraints. We build a dynamic stochastic general equilibrium model with real estate and local government debt risk based on the New Keynesian-Dynamic Stochastic General Equilibrium Model (NK-DSGE) model to investigate the transmission path of local government debt risk under real estate regulation. In addition, we analyze the risk transmission between the real estate market and local government under different tax systems and investigate the shock to household welfare from a local government debt default. The results show monetary policy can effectively control the scale of local government debt to reduce default risk. An increase in property taxes that restrains housing demand can effectively regulate the real estate market. Although reducing taxes can increase macroeconomic output, reducing tax rates on consumption, capital, and labor weakens the liquidity of household assets. Further, lowering taxes increases local government default risk, which reduces household welfare and makes it more difficult for local governments to deleverage. Our findings provide important insights for countries seeking an effective real estate regulation mechanism to curb local government default risk.